Fuzzy strongly pre-irresolute functions - Gowrisankar, N.; Rajesh, N. (Український математичний вісник, 2010)
In this paper, we have introduced and studied a new class of fuzzy irresolute functions, called fuzzy strongly pre-irresolute functions by using fuzzy preopen sets.